TOTAL LYMPHOCYTE COUNT AS A PROGNOSTIC MARKER FOR CD4 COUNT IN RESOURCE LIMITED SETTINGS - G.O., Chukwuma; G. O., Ezeifeka; G.I., Ahaneku; O.M., Chukwuma; F.O., Nwaokorie; S.O., Kalu; N., Ndembi; P.O, Manafa (European Scientific Journal, ESJ, 2013)
Understanding the Total lymphocyte count (TLC) and CD4 relationship could aid design predictive instruments for making clinical decisions during antiretroviral therapy. The aim of this study was to determine the predictive ability of TLC for CD4 count less than or equal to 350cells/mm3. A cross sectional study involving 432 HIV-I infected persons randomly ﻿recruited from the HIV Clinics of Nnamdi Azikiwe University Teaching Hospital (NAUTH) Nnewi, NAUTH Oba and St Charles Borromeo Hospital Onitsha was conducted. Ethical approval was obtained and blood samples were collected. The following were determined; HIV- screening and confirmation using serial testing algorithm with ELISA rapid test kits, CD4 count using Cyflow partec machine and Haematological profile using Sysmex KX21N. Data analysis was carried out using SPSS version 17. Out of the 432 HIV patients involved in this study, females dominated with a population of 274(63.4%) against the males numbering 158(36.6%). The relationship between the TLC cut offs and CD4 count ≤350 cells/mm3 were all statistically significant (P<0.05) except for a TLC value of 2600cells per mm3. At a value of 1200 cells/mm3, TLC had a sensitivity of 25% and specificity of 96% while at 2400 cells/mm3, TLC had a sensitivity of 76% and specificity of 39% for CD4 count of ≤350cells/mm3.TLC was found to have the most significant relationship with CD4 count of all parameters tested using regression analysis. Finally, TLC could serve as a surrogate for CD4 count for monitoring treatment in resource poor areas where facilities for CD4 count may not be available.